Purchase intention towards halal food product among non muslim students of Kangwon National University, South Korea / Azurin Sani …[et al.] - Sani, Azurin; Mohamed Thaheer, Ahmad Shazeer; Syed Omar, Syed Ashrene; Sani, Mawaddah Nasrun; Mohamad, Amiro (Universiti Teknologi MARA, 2021)
This paper aimed to explore the purchasing intention of halal food products among Kangwon National University students in International Trade and Commerce major in South Korea. This study used the Theory of Planned Behavior (TPB) that consists of attitude, subjective norm, and perceived behavioral control that could affect the purchase intention. It also assessed the most influential factor affecting the purchasing intention of halal food. The method used to conduct the survey is questionnaire distribution through blast emails to all Semester 8 Korean Students in the Faculty. The total number of students in the faculty is 354. Thus, the target respondents from the population are 120 students in the faculty. Correlation analysis and regression were utilized to analyze the data and meet the research objectives. The expected outcome from this research project is to analyze the three influential factors; is attitude, subjective norm, and perceived behavioral control that have the most influential effects on purchasing attention. The outcomes of this study, show that attitude does influence the purchasing intention of halal food products among students in Kangwon University, while subjective norm and perceived behavioral control do not affect purchasing intention of the students.